Scientific Approach in Islamic Junior High School Science Textbooks to Facilitate High Order Thinking Skills - Ariyanti Pohan, Lisa; Maulina, Julia; Hasanah, Uswatun; Hardianti, Tuti (International Journal of Engineering and Technology, 2018)
This study aims to analyse textbooks used by students based on the scientific approach as the realization of learning objectives using the 2013 curriculum. This study did several things: first, an investigation of the teaching materials used by students based on the scientific approach, second studied the suitability of the content of textbooks used by students with the syllabus in the 2013 curriculum, thirdly investigating the contribution of textbooks used to higher-order thinking skills. Research method used is mixed methods namely descriptive method and survey study at Islamic Junior High School in Medan. There are 3 textbooks that will be analysed, the textbooks from three different publishers which used by the school. The total number of students who participated in this study were 201 students. Where students who participated in the study were selected based on purposive random sampling through certain considerations, the students come from Islamic Junior High School An Nizam, Islamic Junior High School Ulun Nuha, and Islamic Junior High School Al Fityan, the condition and character of schools are almost same, so is expected the homogeneous sample. The results obtained are: (1) From the three books, the results of conformity assessment with the syllabus in book A are 65%, book B is 80%, and book C 40%; (2) The evaluation results of the textbooks by using the scientific steps find that book A obtained a score of 53 in the low category, book B got a score of 58 in the low category, and book C got a score of 55 also in the low category; 3) The results of the assessment of HOTS ability of students from each school that use books A, B, and C are on the average low category.Â Â Â